Feasibility study for the treatment of Palm Oil Mill Effluent (POME) using electrocoagulation method in Sri Lanka - Wasala M.K.R.T.W. Bandara; B.M.L.A. Basnayake; M.N.M. Shayan; I.M.V.U. Illangakoon; N.A.S. Nimanthika; K.H. Thanushka; H. Satoh (Desalination and Water Treatment)
Palm Oil Mill Effluent (POME) is a significant environmental pollutant due to its high concentrations of chemical oxygen demand (COD), biochemical oxygen demand (BOD), and turbidity. Discharging POME directly into water bodies can have detrimental consequences without proper treatment. While various aerobic and anaerobic treatment technologies have been explored, previous research indicated the limitations of anaerobic ponding systems in achieving adequate effluent quality. To address these challenges, this study investigated the efficacy of electrocoagulation (EC) as a post-treatment method for POME. Using a 15 L reactor equipped with four aluminum electrodes spaced 60 mm apart, laboratory-scale experiments to evaluate the effects of hydraulic retention time (HRT) in hours (hrs) and voltage supply in Volts (V) on POME treatment efficiency. EC significantly improved POME treatment performance by varying HRT (4, 8, and 12 hrs) and voltage (6.5, 9.5, and 16.5 V). Specifically, a combination of 12 hrs HRT and 9.5 V voltage using aluminum electrodes resulted in a 92 % reduction in COD and over 99 % removal of turbidity. These findings highlight the potential of EC as a promising technology to enhance the overall efficiency of POME treatment processes. This method offers a promising approach for POME treatment that aligns with environmental sustainability and regulatory requirements where further study is needed.